Entropy Production Due to Conjugate Natural Convection in a Nanofluid-Filled Enclosure With a Stepped Wall - BOUCHOUCHA, Abd el malik; OZTOP, Hakan F.; BESSAÏH, Rachid; ABU-HAMDEH, Nidal (Engineering Transactions, 2023)
The main aim of this paper is to improve the heat transfer in a square cavity with a body at the left wall filled with a Al2O3/water nanofluid for different geometries. Numerous simulation experiments are conducted. A relative temperature is maintained at the vertical and top horizontal walls while the bottom wall is warm. The finite volume approach is considered to resolve the equations governing the thermal transfer flow in the physical domain based on the SIMPLER algorithm. In this study, different values of the following parameters are considered: Rayleigh number (104 ≤ Ra ≤ 105) and solid volume fraction (0 ≤ ϕ ≤ 0.1) of nanoparticles (NPs). Parameters, such as the Rayleigh (Ra) and Bejan (Be) numbers, thermal conductivity, body’s dimensions, and NPs volume fraction, which directly affect the entropy generation and heat transfer rate, are studied in a particular way. The obtained results show that entropy generation goes ahead with the Ra increase and inverse to the solid volume fraction increase. One can notice that the heat transfer has a proportional relation with ϕ and Ra.